Improving the perceived contribution of sustainable tourism through the residents’ empowerment and support for tourism development: A different age group context - Lorena Bašan; Ivana Perušina; Marija Ham (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu)
This study aims to investigate the relationships of the residents’ empowerment and support for tourism development with the perceived contribution of sustainable tourism and to identify precise attributes among different resident age groups, which can be used to improve the residents’ perceived contribution of sustainable tourism. Research was conducted on a convenience sample of adult Croatian residents using a survey method. The results reveal that empowerment and support for tourism development are essential predictors of perceived sustainable tourism contribution in the group of residents older than 36 years of age. Furthermore, support for tourism development positively affects the perceived contribution of sustainable tourism among younger residents. In addition, the correlation analysis identified stronger relationships between all empowerment attributes and the perceived contribution of sustainable tourism among older residents. In both age groups of residents, all tourism support attributes are positively correlated with a perceived contribution of sustainable tourism. These findings give a comprehensive framework for understanding how the residents’ empowerment and tourism support development shape perceived sustainable tourism outcomes while considering age-related variations in community responses.